2003
DOI: 10.1053/jhep.2003.50327
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant Hepatitis After Grand Mal Seizures: Mechanisms and Role of Liver Transplantation

Abstract: Fulminant liver failure is a rare complication of grand mal seizures with a high mortality, the prognosis being largely determined by the combination of the hepatic and neurologic insults. The mechanisms of acute liver failure secondary to grand mal epilepsy and the place of liver transplantation in this context are poorly defined and are the subject of this report. A series of 6 such patients is presented. All had a history of chronic primary or post-traumatic epilepsy and presented with acute liver failure s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
1
8
0
1
Order By: Relevance
“…This suggests that chemoshock also produces stress on the liver. Our results are in agreement with the reports of Baxter et al [36] and Ichai et al [37] who have reported hepatomegaly and fulminant hepatitis following seizures. Further, the addition of NAC (100 mg/kg, p.o.)…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This suggests that chemoshock also produces stress on the liver. Our results are in agreement with the reports of Baxter et al [36] and Ichai et al [37] who have reported hepatomegaly and fulminant hepatitis following seizures. Further, the addition of NAC (100 mg/kg, p.o.)…”
Section: Discussionsupporting
confidence: 94%
“…[36] and Ichai et al. [37] who have reported hepatomegaly and fulminant hepatitis following seizures. Further, the addition of NAC (100 mg/kg, p.o.)…”
Section: Discussionmentioning
confidence: 99%
“…Fulminant liver failure is a rare complication of grand mal seizures with a high mortality. The mechanisms of acute liver failure secondary to grand mal epilepsy are poorly defined and appear multifactorial, including hypoxia, steatosis and drug-induced components [9].…”
Section: Introductionmentioning
confidence: 99%
“…Liver transplantation may be the only solution for most acute liver failure (ALF) patients but is hindered by severe shortage of organ donors [1]. A bioartificial liver assist device (BLAD) that can provide the critical hepatic functions would be extremely valuable to ALF patients [2].…”
Section: Introductionmentioning
confidence: 99%